Going public : the theory and evidence on how companies raise equity finance - Jenkinson, Tim, 1961-; Ljungqvist, Alexander (Oxford [UK] ; New York : Oxford University Press, 2001)
Over the years, there has been an enormous amount of research into the way companies raise finance from stock markets. There are many reasons for this interest in 'initial public offerings' (IPOs). This book investigates the issues in a non-technical manner, drawing upon international evidence from private sector companies and privatizations.
Includes bibliographical references (p. [207]-221) and index.
nmn 16/07/14
Loans
Keywords: Going public (Securities)